Foraging, diet and community structure in an epigaeic ant (Hymenoptera: Formicidae) assemblage: the role of recruitment - Fowler, H. G. [UNESP] (My University, 1997)
The significance of recruitment systems for community structure of epigaeic ants in a tropical upland forest in southern Brazil was evaluated by examining patterns of spatial occurrence at fixed points. Normal exploratory activity was evaluated with pitfall traps, while the effect of recruitment and diet was evaluated by using honey and sardine baits at the same points. Through techniques developed for environmental impact assessment, the significance of recruitment was evaluated following perturbation, or the placement of bait. Of the 46 species encountered, 15 were sufficiently frequent to study. Of these, only 6 showed significant spatial frequency changes at baits when compared with pitfall trap collections. In one analysis, monthly differences were important for a few smaller species, suggesting thermic limitations, while bait types either increased or decreased spatial point usage. The magnitude of spatial point variation is an index for the strength of recruitment in community organization. Bait types suggest nutritional possibilities of each species. Both recruitment and diet are probably functions of the species composition of the ant community.
Keywords: ant; community structure; diet; foraging; recruitment; Formicidae; Hymenoptera